Finite element analysis of Manila Cathedral Basilica using non-destructive testing results - Piedad, Melmar B.; Antonio, Oscar Victor M. Jr.; Venus, Mary Jane F. (Quezon City College of Engineering, University of the Philippines Diliman, 2014)
This research aimed to assess a heritage masonry structure in the Philippines to predict its behavior when subjected to extreme loads using the data acquired from in-situ non-destructive testing (NDT). In order to do this, various methods were employed for the evaluation of the structure. The Metropolitan Manila Minor Basilica of the Immaculate Conception or more commonly known as the Manila Cathedral in Intramuros, Manila is the subject of this research. Using ultrasonic testing, nondestructive technique of evaluating various materials, certain parameters were acquired through both on-site and material sample testing on laboratory. Confirmation of the results was done through the use of destructive testing (DT). The structural model was created using the commercial structural analysis program SAP2000, which utilized nonlinearity from material testing for more realistic results. To determine the stress and displacement distribution on the structure when subjected to different load types and combinations, strength-based analysis from NDT results and nonlinear modal time history analysis using DT results were performed. For earthquake simulation, the time-history record of 1992 Landers, USA earthquake was utilized to approximate the geologic conditions on the vicinity of the Cathedral. Results of the analyses confirmed assumptions imposed on the material behavior of unreinforced adobe structures: strong in compression and gravity loading, but weak in tension.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Manila Cathedral (Manila, Philippines); Structural analysis (Engineering)